(3eSFhdjI GdhRQGA (B: s (3OQGSI ebGQfI eY GdJWHjb Ydi GdfXGe GdeUQi (B/ s - (3SjO eMeO Hjhei CMeO ahOg s; (3jMji GdLeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JJfGhd GdQSGdI ChLg eSFhdjI GdhRQGA ai cd ef GdeedcI GdeJMOI haQfSG heUQ Pdc ef NdGd GdLhGfH GdJfXjejI GdYGeI ef GdMbjHI GdhRGQjI hGdefUH GdhRGQi (B. (3hjJfGhd GdHMK GdgjFI GdLeGYjI ddhRQGA hGdeSFhdjI GdSjGSjI heSFhdjI GdhRQGA GdLfGFjI hGdeOfjI (B. (3hJhUdJ GdQSGdI Edi JhUjGJ dYdGL CReI eSFhdjI GdhRQGA ef NdGd GdfghV HeDSSI GdHQdeGf heDSSI GdhRGQI hQFjSgG (B: (3hJMLje eDSSI QFGSI GdLeghQjI hJNaja TQhW hELQGAGJ JMQjc eSFhdjI GdhRQGA GdSjGSjI hGdLfGFjI eY EUOGQ JTQjY LOjO gPg GdCNjQIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B665-681s
Keywords: (3GdbGfhf GdYGes; (3GdeSFhdjI GdLfGFjI hGdeOfjI s; (3GdeSFhdjI GdSjGSjI s; (3eSFhdjI GdhRQGA s; (3GdefUH GdhRGQjs; (3GdMbjHI GdhRGQjIs; (3GdgjFI GdLeGYjI ddhRQGAs; (3fTCI GdhRGQI aj GdeedcI GdeJMOIs; (3fTCI GdhRGQI aj aQfSGs; (3fTCI GdhRGQI aj eUQ s; (3SdWI GdJGL s; cabinet committees; Inner cabinet; Individual responsibility; collective responsibility; responsibility penal & responsibility civile; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes